A PROGRAM IN C++ THAT SIMULATES THE HP 48G CALCULATOR - Lorena Lazo, Paul (2005)
The article presents a program in C++ language that emulates the behavior of a HP 48G calculator. For this, we use the concepts that the paradigm of the programming oriented to objects and battery algorithms for the polish notation provide. In the implementation of the program a Borland C++ 4.5 Compiler was used.